2022
DOI: 10.1016/j.lungcan.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding negative prediction performance of solid pulmonary nodule volume AI for ultra-LDCT baseline lung cancer screening risk stratification

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Google's AI algorithm has shown potential in predicting lung cancer risk based on LDCT images, with the authors reporting performance levels similar to or better than those of radiologists (Ardila et al, 2019). Using AI in ultra-LDCT lung cancer screening may significantly reduce the workload of radiologists (Lancaster et al, 2022).…”
Section: Ai For Ct Images Analysis In Lung Cancer Screeningmentioning
confidence: 99%
“…Google's AI algorithm has shown potential in predicting lung cancer risk based on LDCT images, with the authors reporting performance levels similar to or better than those of radiologists (Ardila et al, 2019). Using AI in ultra-LDCT lung cancer screening may significantly reduce the workload of radiologists (Lancaster et al, 2022).…”
Section: Ai For Ct Images Analysis In Lung Cancer Screeningmentioning
confidence: 99%
“…Alternatively, in place of AI differentiating between benign and malignant lung nodules, workload reduction can be achieved by correctly classifying nodules by size. A recent study on the performance of AI for categorization of lung nodules based on volumetric size measurement showed that AI could outperform four experienced radiologists when looking at negative misclassifications, resulting in a possible workload reduction of up to 86.7% [72].…”
Section: Artificial Intelligence In Lcsmentioning
confidence: 99%
“…4). Lancaster et al recently evaluated this type of deep-learning tool in 283 participants from the Moscow lung-cancer screening program who had at least one solid lung nodule [41]. CT examinations were analyzed independently by five experienced thoracic radiologists.…”
Section: Lung Nodule Segmentation and Characterizationmentioning
confidence: 99%